2014
DOI: 10.1128/aem.03344-13
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Metabolites Highlights the Microbial Interactions and Role of Acetobacter pasteurianus during Cocoa Bean Fermentation

Abstract: Four cocoa-specific acetic acid bacterium (AAB) strains, namely, Acetobacter pasteurianus 386B, Acetobacter ghanensis LMG 23848 T , Acetobacter fabarum LMG 24244 T , and Acetobacter senegalensis 108B, were analyzed kinetically and metabolically during monoculture laboratory fermentations. A cocoa pulp simulation medium (CPSM) for AAB, containing ethanol, lactic acid, and mannitol, was used. All AAB strains differed in their ethanol and lactic acid oxidation kinetics, whereby only A. pasteurianus 386B performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 51 publications
6
102
1
Order By: Relevance
“…The species A. pastorianus and G. oxydans were detected by PCR-DGGE during both fermentations. A. pasteurianus is a species commonly found at the end of cocoa fermentation, capable of oxidizing both ethanol and lactic acid produced by yeast and LAB, respectively, contributing to increased acidity and temperature, and death of the bean (Moens et al 2014). The temperature of fermentations reached 50°C (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…The species A. pastorianus and G. oxydans were detected by PCR-DGGE during both fermentations. A. pasteurianus is a species commonly found at the end of cocoa fermentation, capable of oxidizing both ethanol and lactic acid produced by yeast and LAB, respectively, contributing to increased acidity and temperature, and death of the bean (Moens et al 2014). The temperature of fermentations reached 50°C (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Lactate is metabolized via lactate dehydrogenase and further metabolized into acetate (26). It has been reported that A. pasteurianus strains accumulate acetoin, when incubated with lactate (23)(24)(25). Indeed, two different pathways for acetoin formation are annotated.…”
Section: Methodsmentioning
confidence: 99%
“…As a central finding, the concerted use of lactate and ethanol enables optimum fluxes with regard to growth and energy metabolism. Considering recent insights into the extracellular and molecular fluxes of LAB during cocoa fermentation (12,20,23,30), this suggests that the efficiency of AAB depends on compositional traits provided by LAB and yeasts during the initial fermentation process so that the overall success of cocoa fermentation requires a well-balanced microbial consortium. …”
mentioning
confidence: 99%
See 2 more Smart Citations